The Influence of Culture and Legal Origin Toward Earnings Management of Manufacture Firms Listed in NYSE - Istiqomah, D F (KnE Social Sciences, 2018)
This study examines the influence of culture and legal origin toward earnings management practice. Based on a sample of 87 manufacture firms that come from 18 countries listed in the New York Stock Exchange for three years, 2009–2011, the result shows that firms come from countries of civil-law system with low cultural secrecy level having lower earnings management behavior compared to firms coming from countries of common-law system with high cultural secrecy level. This research gives empiric evidence that culture is an important factor that can influence finance report quality. Keywords: cultural secrecy, legal origin, earnings management